2008
DOI: 10.1248/bpb.31.546
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Some Characteristics of Peroxisomes in Immortalized Human Trophoblast Cells

Abstract: Reports about the peroxisomes of rat liver are abundant, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] but much less is known about those of other rat organs. 17,18) Furthermore, there are few reports about peroxisomes of human liver, 2,3,5,6,[8][9][10]14,19) and very few about those of other human organs. [20][21][22] There are three kinds of trophoblasts in the placenta: cytotrophoblasts, syncytiotrophoblasts and extravillous trophoblasts. Each of the three plays important roles in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…33,34) In the preceding paper, using morphological and biochemical methods, we clarified that clofibric acid induces the proliferation of microperoxisomes in human trophoblast cells. 4) We tried to purify the TCL-1 peroxisomes by a discontinuous Nycodenz density gradient centrifugation, but a small number of mitochondria contaminated the peroxisomal fractions (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…33,34) In the preceding paper, using morphological and biochemical methods, we clarified that clofibric acid induces the proliferation of microperoxisomes in human trophoblast cells. 4) We tried to purify the TCL-1 peroxisomes by a discontinuous Nycodenz density gradient centrifugation, but a small number of mitochondria contaminated the peroxisomal fractions (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…3) In the preceding paper, we clarified that clofibric acid induces the proliferation of trophoblast cell microperoxisomes. 4) Rat liver cells are useful for experiment of peroxisomes, but they do not secrete hormone. However, trophoblast cells secrete both steroid hormone and protein hormone.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Both PPARα and PPARδ agonists are able to induce the expression of ACO, the rate-limiting enzyme in peroxisomal β-oxidation, in different cell types (Mochizuki et al 2008;Nagasawa et al 2006). ACO is expressed in the human placenta (Hashimoto et al 2008). We here found that ACO is expressed in the rat placenta at midgestation, and that ACO expression is enhanced in the diabetic placenta when compared to controls.…”
Section: Discussionmentioning
confidence: 48%